ANALISIS KEUNGGULAN KOMPARATIF DAN KOMPETITIF KOMODITAS KENTANG DAN KUBIS DI WONOSOBO JAWA TENGAH - -, SAPTANA; -, SUMARYANTO; FRIYATNO, SUPENA (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 3, No. 1 Februari 2003)
The Agricultural Development in Indonesia is focused to enhance the structure of production that more diversified through sustainable agribusiness approach. With this context, based on the demand side horticulture commodities especially potato and cabbage are feasible to developed by increasing of production area, cropping intensity, and productivity. This paper is proposed to: (a) conducting financial and economic analysis of both commodities, (b) comparative and competitive analysis, (c) measuring the divergences and government policy impact, (d) formulating the incentive policy interim of both commodities development. By Policy Analysis Matrix (PAM) method, the result showed that both commodities have comparative and competitive advantage, which is indicated by DRC and PCR less then 1 .The calculation showed the DRC for potato is arranging 0.239 – 0.306 and for cabbage is 0.622-0.660. PCR for potato is arranging 0.413-0.468 and for cabbage is 0.854-0.875. That mean for producing the one unit value added of both commodities can be achieved by using less then one unit of the domestic resource factors. In other word, in Wonosobo Central Java both commodities are more profitable to produce than import.
Keywords: Comparative dan Competitive Advantage, Policy Analysis Matrix, Potato and Cabbage Commodities